A NEW CLASSIFICATION OF PALEOZOIC RADIOLARIA - Afanasieva M.S. (My University, 2002)
A new classification of Paleozoic Radiolaria is developed. The subphylum Radiolaria includes two classes, i.e., Pheodaria and Polycystina. The class Polycystina is composed of the following seven orders: Sphaerellaria Haeckel, 1881, Stauraxonaria Afanasieva, 2000, Aculearia Afanasieva, 1999, Albaillellaria Deflandre, 1953, emend. Afanasieva, 1999, Pylomaria Afanasieva, 1999, Nassellaria* Ehrenberg, 1847, and Collodaria* Haeckel, 1881 (* unknown in the Paleozoic). The diagnoses of 87 radiolarian taxa are given, among them five orders, 18 superfamilies, 28 families, and 36 subfamilies.
Keywords: Paleozoic; Paleozoic; Палеозой